The Effects of 6% Hydroxyethyl Starch-Hypertonic Saline in Resuscitation of Dogs with Hemorrhagic Shock - Barros, Joao M. P. [UNESP]; do Nascimento, Paulo [UNESP]; Marinello, Joao Luiz P. [UNESP]; Braz, Leandro Gobbo [UNESP]; Carvalho, Lidia R. [UNESP]; Vane, Luiz Antonio [UNESP]; Castiglia, Yara Marcondes Machado [UNESP]; Braz, José Reinaldo Cerqueira [UNESP] (Lippincott Williams & Wilkins, 2011)
BACKGROUND: Hemodynamic and global oxygen transport variables have failed to reflect splanchnic hypoperfusion, resulting in a failure to recognize inadequately treated hemorrhagic shock. Volemic expansion after fluid resuscitation is essential to improve global and regional oxygen in hemorrhagic shock. We hypothesized that, in contrast to conventional plasma expanders, the smaller volemic expansion from 7.5 NaCl/6% hydroxyethyl starch (HHES) solution administration in hemorrhagic shock may provide lesser systemic oxygen delivery and gastric perfusion. We used hemorrhaged dogs to compare intravascular volume expansion and the early systemic oxygenation and gastric perfusion effects of fixed fluid bolus administration, which are usually used in clinical situations with severe hemorrhage, of HHES, lactated Ringer (LR), and 6% hydroxyethyl starch (HES) solutions.METHODS: Thirty dogs were bled (30 mL . kg(-1)) to hold mean arterial blood pressure at 40 to 50 mm Hg over 45 minutes and were resuscitated in 3 groups: LR (n = 10) at 3:1 ratio to shed blood; HES (mean molecular weight 130 kDa, degree of substitution 0.4) (n = 10) at 1:1 to shed blood; and HHES (n = 10), 4 mL . kg(-1). Intravascular volume expansion (Evans blue and hemoglobin dilution), hemodynamic, systemic oxygenation, venous-to-arterial CO(2) gradient (P (v) over bar -aco(2)), and gastric intramucosal-arterial Pco(2) gradient (Pco(2) gap) variables were measured at baseline, after 45 minutes of hemorrhage, and 5, 45, and 90 minutes after fluid resuscitation.RESULTS: HHES increased blood volume because of the high volume expansion efficiency, but intravascular volume expansion with this solution was the smallest of the solutions (P < 0.05). All 3 solutions induced a similar hemodynamic performance but HHES showed lower mixed venous Po(2) and higher systemic oxygenation extraction, P<(v)over bar>-aco(2), and Pco(2) gap than LR and HES (P < 0.05).CONCLUSIONS: In dogs submitted to pressure-guided hemorrhagic shock and fixed-volume resuscitation, the smaller intravascular volume expansion from HHES solutions provides worse recovery of systemic oxygenation and gastric perfusion compared with LR and HES solutions despite its high volume expansion efficiency, which was limited by low infused volume. (Anesth Analg 2011;112:395-404)